Kierkegaard, the Forerunner of Presuppositional Apologetics - Oganessian, Armen (Philosophia reformata, 2025)
This paper argues that Kierkegaard critiques both inductive and deductive arguments for establishing biblical truths. His contention with them arises from his belief that the human mind, restricted by its cognitive limitations, lacks the requisite categories to know God. Essentially, without the incarnation of Christ, the human intellect lacks the object for the subject of theology. This, coupled with his belief that one can only directly encounter Christ in the Bible, leads Kierkegaard to advocate for a reliance on Scripture as the sole source of knowledge of God. He argues that proofs, whether historical or speculative, create an epistemological barrier between the individual and Christ. Historical arguments, in Kierkegaard’s view, treat truth as a mere hypothesis, thereby distancing believers from a genuine encounter with God. Likewise, speculative proofs, by abstractly presenting Christian truths, create a similar distance. Thus, I contend that Kierkegaard should be recognized as a precursor to presuppositionalism.